Effectiveness of high-flow nasal oxygen therapy in management of acute hypoxemic and hypercapnic respiratory failure - Norkienė, Ieva; d’Espiney, Raquel; Martin-Lazaro, Juan F. (Acta medica Lituanica, 2019)
Background. High-flow nasal oxygen therapy (HFNOT) therapy has been increasingly used in patients with acute hypoxemic (Type I) respiratory failure (RF). Meanwhile indications and clinical effectiveness of HFNOT in patients with hypercapnic (Type II) RF remain controversial. The aim of our study was to evaluate the outcomes of primary HFTNOT in patients with hypoxemic and hypercapnic RF. Material and Methods. We conducted a retrospective observational study of patients diagnosed with severe community acquired pneumonia (CAP), who required HFNC oxygen therapy for hypoxemia. Primary end-point was intubation or escalation to NIV rate after HFNOT. The secondary endpoint was the 30-day mortality after an admission regardless of the cause. Results. Analysis was conducted on all 51 (n = 51) patients. Of these, 32 (63%) were diagnosed with Type I RF and 19 (37%) with Type II RF. The partial pressure of arterial carbon dioxide (PaCO2) in Type I RF patients was 34.05 mmHg at admission and decreased to 33.07 mmHg after 1 hour of HFNOT. In patients with Type II RF PaCO2 decreased from 56.47 to 54.97 mmHg. In Type I RF successful outcome was achieved in 25 patients (78%) compared to 11 patients (58%) with Type II RF. Escalation was required in seven patients with Type I RF and eight patients in Type II group. There were no mortalities in our population group. Conclusions. Our data suggest that HFNOT can be effectively used in Type I and Type II RF. Clinicians should be cautious identifying patients at risk of escalation. A larger population group study is needed to identify predictors of HFNOT failure.
Keywords: high flow oxygen therapy; respiratory failure; non-invasive ventilation